ESTIMATION OF HYBRID VIGOUR, COMBINING ABILITY AND GENE ACTION USING (LINE × TESTER) ANALYSIS IN MAIZE - & et al., Mutlag (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Field experiment was conducted at field of Fallujah- Anbar Governorate/ Iraq, during the two seasons of 2017. Seeds of eight maize inbred lines were cultivated, and line × tester method was used to produce 16 crosses. The seeds of parents were cultivated and crosses in the fall season of 2017 in a randomized complete block design with three replicates. The objectives of the study were to estimate gene action, hybrid vigour, and the effects of general and specific combination abilities of the inbred lines  and to evaluate test cross performance of the hybrids for grain yields and yield related traits. There were significant differences between parents and their crosses for all studied traits. The results showed that crosses (ZM12 x ZM51W) and (ZM12 x ZM43W) gave the highest hybrid vigour in grain yield (39.32% and 31.62% respectively) to the best parents. The two crosses also were superior in the plant grain yield (222.29 and 217.15 gm. plant -1).The specific combination ability components were larger than the general combination ability components. The dominance genetic variation was more important than the genetic variation additive. The heritability in its narrow sense was low ranging between 2.17% for grain yield.plant-1 and 25% for Leaf area, and this led to a high degree of dominance on the one for all the studied traits except leaf area. It can be concluded that it is possible to use some parents which outperformed others of crosses, because most of traits were under the influence of dominant  and over dominant gene effects.